Second international symposium on environmental biotechnology, 4-6 July 1994, Brighton UK : [proceedings] - Institution of Chemical Engineers (Great Britain); European Federation of Biotechnology; Biotechnology '94 (2nd : 1994 : Brighton, UK) (Warwickshire, UK : Inst. of Chemical Engineers, 1994)
55